PENGARUH PENGELOLAAN KEUANGAN DAERAH, PEMANFAATAN TEKNOLOGI DAN SISTEM AKUNTANSI KEUANGAN DAERAH TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH (Studi Kasus Pada Desa Se-Kecamatan Gatak) - Siti Nur Cahyani Subariningsih; Desy Nur Pratiwi; Hadi Samanto (CV. Denasya Smart Publisher, 2025)
This study aims to analyze the influence of regional financial management, technology utilization, and regional financial accounting systems on the quality of regional government financial reports. The method used in this study is quantitative. Data were obtained by distributing questionnaires to respondents who had been determined using purposive sampling techniques. Data analysis techniques used in this study include descriptive statistics, validity tests, reliability tests, classical assumption tests, and multiple linear regression analysis. The results showed that regional financial management had a significant effect on the quality of regional government financial reports with a t count of 6.333> t table 1.668 and a significance of 0.000 <0.05. The use of technology had a significant effect on the quality of regional government financial reports with a t count of 5.837> t table 1.668 and a significance of 0.000 <0.05. The Regional Financial Accounting System had a significant effect on the quality of regional government financial reports with a t count of 4.102> t table 1.668 and a significance of 0.000 <0.05.